Evaluation of physiological quality seeds of Mimosa flocculosa of different colors submitted to pre-germinative treatments (Revista de Ciências Agroveterinárias, 2014)
The objective of this study was to evaluate the efficiency of pre-germination treatments on the germination of Mimosa flocculosa clear and dark seeds, collected in different years (Lots 1 and 2). The work was divided into two stages: the first, seeds were treated to break dormancy (immersion in cold water for 24 hours, soaking in hot water (98°C) for 18 hours, immersion in concentrated sulfuric acid for one minute and three minutes and seeds intact (control). In the second stage, the seeds, of two lots, were visually separated into two color classes: clear and dark seeds, and submitted the best treatment for dormancy breaking of the first stage. In both stages, the seeds were sterilized with sodium hypochlorite at 2% for three minutes and placed in a germination chamber with constant light at 25°C. Percentage and speed of germination were analyzed. The experimental design was completely randomized with four replications of 25 seeds for each treatment, and the treatment means were compared by Tukey test (p
Keywords: Bracatinga-de-Campo-Mourão; Germination; Dormancy; Physiological quality.